Nanocompósitos de polietileno e amido termoplástico com diferentes nanoestruturas baseadas em nanotubos de haloisita e TiO2 - Anderson Maia Peres (2014)
Plastic bottles and bags are responsible for consuming the largest amount of plastics processed in Brazil and polyethylene is the most widely used polymer for this purpose. Thus, large quantities of waste are generated with the inappropriate disposal of such materials. One way to minimize this problem is the development of new materials that would be able to biodegrade in the environment without producing harmful waste to human health and environment. Thus, this study aims to develop new materials capable of maintaining their properties during their lifespan and subsequently biodegrade when properly discarded in the environment. For this, blends of thermoplastic starch and polyethylene (50/50% wt.) were initially produced by conventional routes in order to have comparable mechanical properties to pure polyethylene. Then, halloysite nanotubes and TiO2 based nanostructures, such as TiO2 nanoparticles, hydrogen titanate nanotubes and titania nanotubes were dispersed in thermoplastic starch/low density polyethylene blends. Therefore, considering the various types of nanostructures, the work was divided into two parts. The first part consisted in obtaining nanocomposites of thermoplastic starch/low density polyethylene with halloysite nanotube in concentrations of 2, 5 and 8% by weight. Results showed that the nanocomposite containing 8% by weight with halloysite nanotubes had higher mechanical properties than low density polyethylene 29% in modulus and 9% in elongation at fracture. In the second part, hydrogen titanate nanotubes and titania nanotubes were synthesized from commercial TiO2 nanoparticles. The materials were characterized and subsequently incorporated into thermoplastic starch/low density polyethylene blends at concentrations of 0.2 to 2% by weight. The mechanical properties of all the nanocomposites were evaluated, whereas thermal, optical and photodegradation properties were evaluated for nanocomposites containing 2% by weight of the nanocomponents. The results showed successful conversion of TiO2 nanoparticles to hydrogen titanate and titania nanotubes with high surface area in relation to precursor material. The mechanical properties were higher with the incorporation of hydrogen titanate nanotubes and titania compared to TiO2 nanoparticles. The nanocomposite containing 0.2wt% of hydrogen titanate nanotubes was able to increase ~107 % the modulus in comparison with low density polyethylene. The incorporation of TiO2 nanoparticles and titania nanotubes resulted in larger changes in the mechanical properties of the materials due to photodegradation. Thus, novel nanocomposites were obtained by different processing techniques, such as pressed films, extruded and injected materials, and the incorporation of nanomaterials in blends of thermoplastic starch/low density polyethylene was justified by the improvements in the observed properties.